Implementation of Differentiated Learning in Indonesian Language Courses: Realizing Freedom of Learning - Muktamar, Ahmad; Fatmawati, Fatmawati; Hardiyanti, Hardiyanti (Education and Talent Development Center Indonesia (ETDC Indonesia), 2023)
The low level of fulfillment of learning needs is an obstacle for students; besides that, the use of a curriculum that is still based on a rote system and the lack of diverse values result in students being passive in the teaching and learning process. As students have a variety of characteristics that must be met, one way of learning diversity is Indonesian. This research aims to see the results of differentiated learning in the implementation of the independent curriculum in Indonesian language subjects held in class IX-A at MAS As'adiyah Putri Sengkang as the subject of research. Then the approach taken is qualitative with a descriptive analysis method, which is carried out in two parts, namely activity analysis and other files. The results obtained show that differentiated learning is suitable for practice in the classroom environment at school as part of the learning requirements in Indonesian language lessons. So the hope is that students can develop their learning activities optimally. This can be seen in the evaluation section, which shows the diversity that exists within each student.